Simulation study of template matching authentication technology based on nuclear resonance fluorescence - Man Zhou; Yu Wang; Qifan Chen; Quanhu Zhang (AIP Advances, 2025)
Template matching authentication technology is a critical means of protecting sensitive information, with widespread applications in security monitoring and verification. Nevertheless, the intrusiveness of this technology risks the leakage of the verified party’s sensitive information. To address this issue, we propose a method combining nuclear resonance fluorescence (NRF) technology with template matching authentication technology. The template gamma spectrum derived from NRF-based template matching authentication contains no sensitive information and can accurately verify the authenticity of special nuclear materials. We mainly investigated the principles of encrypted authentication based on NRF and the complete verification of the experimental objects. Using Monte Carlo simulations, we generated the template gamma spectrum during the verification, as well as the experimental objects’ gamma spectrum. By identifying six experimental objects, we found that the NRF-based template matching authentication technology could correctly identify encrypted experimental objects’ authenticity, indicating the technology’s effectiveness.